Dewan Perwakilan Daerah dalam Persfektif Sistem Pemerintahan Republik Indonesia - Sri Sundari (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The background of this research is based on the phenomenon that the function of the Regional Representative Council (DPD-RI) tends to be limited to issues related to regional autonomy policies. As a result, the involvement of DPD-RI in carrying out its functions as part of a representative institution is less than optimal. The purpose of research of The Regional Representative Council of the Republic of Indonesia (DPD-RI) was conducted to evaluate the functions of DPD-RI and was focused on the effort to answer how DPD implements its legislation, representation, deliberation, scrutinize, recruitment and training functions. The research method used qualitative method to build explanations about the functions implemented by DPD. The result of the research shows that DPD has yet optimize its functions because of the problem of original power, legislation limitation, and its deliberation was not binding. Therefore, it is necessary to amend The UUD 1945 to strengthening DPD authority and to establish a convention which makes DPD deliberations bind the other state institutions.